A errância no romance contemporâneo: uma leitura de A Caverna, de José Saramago, e A Ignorância, de Milan Kundera - Galvão, Aline Scavazini de Matos (2014)
The aim of this research is to analyze how the form of the novel works the wandering theme in the novels of José Saramago and Milan Kundera, comparing them to the axis of the characters to answer the following questions: how the exile lived by characters (un)consacrates the image of wanderers? How this can give a new signification to the idea of identity, understood as a product of relation to the country they came from? Some hypothesis raised: the separation of homeland gives to the outcasts a critical and sensitive consciousness about the relationship between people and their land. The novel, as form of the transcendent homelessness, captures the wanderer with a new image and updates his critical view. The essayistic form, in both novels, contributes to the thematic discussion, being a compositional element of the works. As theoretical axis, we stand out the ideas of Lukács, Adorno and Walter Benjamin, as well critical texts of José Saramago and Milan Kundera as fundament to the creation of poetics of the novel. Regarding the wandering theme, we choose the studies of Michel Maffesoli and Édouard Glissant. The comparative method gave us a more in-depth debate about the wandering theme and how the novel forms echoes the contemporary dilemma regarding notions of identity and globalization.